Fetal Myocardial Performance (Tei) Index in Fetal Hemoglobin Bart’s Disease - Luewan, S.; Tongprasert, F.; Srisupundit, K.; Tongsong, T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: To assess the effectiveness of Tei index in differentiating fetal Hb Bart’s disease in pregnancies at risk in the first half of pregnancyMaterials and Methods: Pregnancies meeting the inclusion criteria were consecutively recruited to the study. The inclusion criteria were as follows: 1) singleton pregnancies, 2) gestational age of 12 – 20 weeks, 3) at risk of Hb Bart’s disease, 4) confirmed fetal diagnosis of Hb Bart’s disease. Fetuses with frank hydrops fetalis or fetuses with chromosomal abnormalities or structural anomalies were excluded. Tei index was performed and immediately recorded before invasive prenatal diagnosis was performed. Results: Of 152 fetuses, 50 were finally proven to be affected by Hb Bart disease, and the remainder was unaffected. Mean (± SD) Tei index were 0.48 ± 0.07 and 0.54 ± 0.08 in group of unaffected and affected fetuses, respectively. The mean difference was 0.05 which was statistically significant (p < 0.001). Likewise, mean (± SD) isovolumetric contraction time (ICT) in normal fetuses were also significantly different from that of affected fetuses.Conclusion: In the first half of pregnancy, Tei index in the fetuses with Hb Bart's disease was significantly higher than that in normal fetuses implying that Tei index may be a novel useful and non-invasive tool for early detection of fetal Hb Bart’s disease among pregnancies at risk.
Keywords: heart; echocardiography; ultrasound-doppler; fetus